Choroidal neovascularization secondary to Best’s vitelliform macular dystrophy in two siblings of a Malay family - Koh, Alisa Victoria; Tan, Jin Poi; Ismail, Shatriah; Embong, Zunaina; Ngah, Nor Fariza (Dove Medical Press, 2014)
Best’s vitelliform macular dystrophy complicated with choroidal neovascularization is rare in children. We report three children from a Malay family of five siblings with Best’s vitelliform macular dystrophy, in which two of them subsequently developed choroidal neovascularization. The possible pathogenesis of this rare condition is described and highlighted in this report.